ECOPEDAGOGI: MEMBANGUN SIKAP MENCINTAI LINGKUNGAN DALAM PEMBELAJARAN PENDIDIKAN AGAMA KRISTEN - Hasugian, Johanes Waldes; Lesilolo, Herly Janet; Huliselan, Mus J (P3M STT Kristus Alfa Omega, 2022)
Ecological awareness is a joint effort to create humans who love and are friendly to the environment in the midst of a mass of people who damage and overexploit the environment. Â This research is carried out by a descriptive â€“ analytical method, which seeks to describe various things related to environmental issues and pedagogical approaches. Â This research found that education is an ecopedagogy laboratory, which is a means for students to be trained in ecological awareness, namely through the application of curriculum and educational programs that goes green.